2014
DOI: 10.3109/21691401.2014.966192
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo performance of supersaturable self-nanoemulsifying system of trans-resveratrol

Abstract: To develop an optimized supersaturable self-nanoemulsifying drug delivery system (S-SNEDDS) in order to improve the oral bioavailability of trans-resveratrol (t-RVT), together with surmounting poor aqueous solubility, enterohepatic recirculation and controlling drug precipitation, by employing a precipitation inhibitor (PPI) that is, hydroxypropyl methylcellulose (HPMC). The long-term stability of a previously reported formulation optimized long chain triglycerides (OPT LCT-SNEDDS), consisting of Lauroglycol F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Recently, oral nanoemulsions have been investigated as potential vehicles for enhancing therapeutic activities and bioavailability of various biologically active drug molecules (Laxmi et al 2015, Obitte et al 2014, Singh and Pai 2016, Thomas et al 2012. Nanoemulsions are thermodynamically stable lipid based drug delivery systems which are composed of oil, surfactant, cosurfactant, and water having the droplet size in the magnitude of nanometers .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, oral nanoemulsions have been investigated as potential vehicles for enhancing therapeutic activities and bioavailability of various biologically active drug molecules (Laxmi et al 2015, Obitte et al 2014, Singh and Pai 2016, Thomas et al 2012. Nanoemulsions are thermodynamically stable lipid based drug delivery systems which are composed of oil, surfactant, cosurfactant, and water having the droplet size in the magnitude of nanometers .…”
Section: Introductionmentioning
confidence: 99%
“…Th e authors alone are responsible for the content and writing of the paper. negative or aggravated signs in hypotension or hemodynamic parameters (Singh and Pai 2014). Despite the lack of diff erences in SvO 2 , arterial lactate, and oxygen delivery, the improvement in urine output and in the doses of norepinephrine indicate benefi cial eff ects on tissue hypoperfusion.…”
Section: Declaration Of Interestmentioning
confidence: 94%
“…In addition to the precipitation inhibition effect, the inclusion of HPMC E5LV in the S-SNEDDS can significantly reduce the excretion effect of P-glycoprotein and multi-resistant proteins to improve systemic exposure levels of the model drug ezetimibe (82,83). The S-SNEDDS formulation of trans-resveratrol (t-RVT) resulted in the formation of a nanoemulsion, and the pharmacokinetic study indicated that the AUC0-8h of the S-SNEDDS formulation increased by nearly 1.33-fold in the presence of the precipitation inhibitor HPMC (84).…”
Section: (1) Formulation Aspectsmentioning
confidence: 99%